The effect of breastfeeding on postpartum glucose tolerance and lipid profiles in women with gestational diabetes mellitus - Alexis Shub; Manisha Miranda; Harry M. Georgiou; Elizabeth A. McCarthy; Martha Lappas (BMC, 2019)
Abstract Background We aimed to investigate the association of breastfeeding on postpartum glucose levels and lipid profiles in women diagnosed with gestational diabetes mellitus (GDM) and women without GDM. Methods We performed a secondary analysis of a cohort study of 243 women, 159 women with GDM and 84 normally glucose tolerant women between 2012 and 2017. At approximately 6-10 weeks postpartum, we measured fasting blood glucose and plasma lipid levels. Breastfeeding behaviour was self-defined as exclusive breastfeeding or not exclusive breastfeeding. Results The mean (SD) glucose in the group of women who breastfed exclusively was 4.6 (0.49) mmol/L, compared to 4.9 (0.58) mmol/L (95% CI 0.45, 0.15, p <  0.001) among women who did not exclusively breastfeed. Among women with GDM, the reduction in fasting glucose in women who were breastfeeding was 0.22 mmol/L (95% CI 0.39, 0.05, p = 0.004), and in women who were not GDM, the reduction was 0.14 mmol/L (95% CI 0.37, 0.09, p = 0.24,). After adjustment for GDM status in pregnancy, maternal body mass index (BMI), maternal age and ethnicity, and exclusive breastfeeding was associated with a decreased fasting glucose of 0.19 (95% CI 0.318, 0.061, p = 0.004). After similar adjustment, there was no significant difference in triglycerides, high density lipoprotein cholesterol or low-density lipoprotein cholesterol between women who were breastfeeding and women who were not breastfeeding. Conclusions Breastfeeding is associated with a reduction in fasting glucose levels postpartum, but not maternal lipid profile. Breastfeeding may play a role in reducing glucose intolerance in women who have had GDM.